Synergistic growth inhibition by sorafenib and vitamin K2 in human hepatocellular carcinoma cells (Clinics, 2012)
OBJECTIVE: Sorafenib is an oral multikinase inhibitor that has been proven effective as a single-agent therapy in hepatocellular carcinoma, and there is a strong rationale for investigating its use in combination with other agents. Vitamin K2 is nearly non-toxic to humans and has been shown to inhibit the growth of hepatocellular carcinoma. In this study, we evaluated the effects of a combination of sorafenib and vitamin K2 on the growth of hepatocellular carcinoma cells. METHODS: Flow cytometry, 3-(4,5-dimethyl-2-thiazolyl-2,5-diphenyl-2H-tetrazolium bromide) and nude mouse xenograft assays were used to examine the effects of sorafenib and vitamin K2 on the growth of hepatocellular carcinoma cells. Western blotting was used to elucidate the possible mechanisms underlying these effects. RESULTS: Assays for 3-(4,5-dimethyl-2-thiazolyl-2,5-diphenyl-2H-tetrazolium bromide) revealed a strong synergistic growth-inhibitory effect between sorafenib and vitamin K2. Flow cytometry showed an increase in cell cycle arrest and apoptosis after treatment with a combination of these two drugs at low concentrations. Sorafenib-mediated inhibition of extracellular signal-regulated kinase phosphorylation was promoted by vitamin K2, and downregulation of Mcl-1, which is required for sorafenib-induced apoptosis, was observed after combined treatment. Vitamin K2 also attenuated the downregulation of p21 expression induced by sorafenib, which may represent the mechanism by which vitamin K2 promotes the inhibitory effects of sorafenib on cell proliferation. Moreover, the combination of sorafenib and vitamin K2 significantly inhibited the growth of hepatocellular carcinoma xenografts in nude mice. CONCLUSIONS: Our results determined that combined treatment with sorafenib and vitamin K2 can work synergistically to inhibit the growth of hepatocellular carcinoma cells. This finding raises the possibility that this combined treatment strategy might be promising as a new therapy against hepatocellular carcinoma, especially for patients with poor liver tolerance.